Are we learning from disasters? Examining investigation reports from National government bodies. (August 2021) - Filho, Anastacio Pinto Goncalves; Ferreira, Adonias Magdiel Silva; Ramos, Magna Fernandes; Pinto, Anderson Rogério Albuquerque Pontes
Graphical abstract: Highlights: Conditions for learning from investigation of disasters. Depth of an investigation is an important condition for learning from disasters. Investigations of disasters may effectively contribute to learning from disasters. Recommendations are one of the most important steps in a disaster investigation. Abstract: The purpose of this research is to examine if investigations disasters carried out by Brazilian government effectively contribute to learning from disasters. In order to do this, a set of conditions that potentially support learning from disasters was established and a set of disaster investigation reports issued by four government bodies were evaluated. The selected reports were those of disasters deemed the worst that had occurred in last 20 years. The results demonstrate that all four government bodies failed to take time to address the factors at the macro level, i.e. social, political, and economic factors in their disaster investigations. Although organisational factors were addressed by all four investigations, none of them addressed cultural factors in their investigations. The investigations carried out by one government bodies were limited in contributing to learning from the disasters investigated, because it did not present a detailed description of the disaster and generate recommendations for all levels of the system (government, all sectors and organisations).